Effects of Academic dishonesty on research production in the light of Total Quality Management- an Empirical Study on Malaysian Educational Institutions – Malaysia - Ibrahim, Mikail; Ahmad, Essamomudin; Al-Harrasi, Saif Darwish Said; Ibrahim, Mohamed El-Taib (Journal of Educational and Psychological Sciences, 2020)
The field study aimed to investigate the causal relationship between the indicators of cognitive plagiarism represented by weak research skills, lack of deterrent punishment, different culture, certainty of impunity, peer behavior, feedback on the one hand, and the will to plagiarism on the other. It also aimed to examine the relationship between the will of plagiarism and plagiarism behavior and its role on overall quality in Malaysian educational institutions. The study followed the descriptive approach. The study sample consisted of 768 students (males = 292, females = 476). They were appointed by way of random stratified. The result of the analysis showed that the indicators of cognitive plagiarism have a positive and strong statistical relationship with the will of plagiarism, and that plagiarism has a positive statistical relationship with the behavior of cognitive plagiarism. In addition, the study revealed that the behavior of cognitive plagiarism has a strong statistical relationship with total quality factors. This finding indicates that intentional or unintentional cognitive plagiarism affects overall quality at all levels. The study recommends amending university regulations on offenses of scientific plagiarism. In addition, the development of universal laws of regulations and procedures by global educational bodies.
Keywords: Academic Dishonesty; Research Production; The Comprehensive quality